2021
DOI: 10.1111/jtxs.12618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rheological properties of the liquid carrier on the in vitro swallowing of solid oral dosage forms

Abstract: Solid oral dosage forms (SODF) are the most popular oral drug delivery forms, but they can be difficult to swallow, especially for patients suffering from swallowing disorders. This study investigated the dynamics of different combinations of liquid carriers and SODF during the oral phase of swallowing using an in vitro model. The rheological properties of the carriers were characterized using shear and extensional rheometry, and their effect on bolus velocity, bolus shape, post‐swallow residues, and SODF posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Most studies looking at the effect of viscosity on swallow safety are concerned with the characteristics of the bolus such as size, shape, and cohesion (Gould et al, 2017; Hadde et al, 2021; Hadde & Chen, 2021; Lavoisier et al, 2021), but focus less on how viscosity affects suckling, the acquisition and intraoral aspect of feeding prior to the swallow (see Mayerl et al, 2021). Suckling performance will depend on how much intraoral pressure the infant can generate, and how easily milk is able to flow out of the nipple.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies looking at the effect of viscosity on swallow safety are concerned with the characteristics of the bolus such as size, shape, and cohesion (Gould et al, 2017; Hadde et al, 2021; Hadde & Chen, 2021; Lavoisier et al, 2021), but focus less on how viscosity affects suckling, the acquisition and intraoral aspect of feeding prior to the swallow (see Mayerl et al, 2021). Suckling performance will depend on how much intraoral pressure the infant can generate, and how easily milk is able to flow out of the nipple.…”
Section: Discussionmentioning
confidence: 99%
“…There are two potential mechanisms to explain this. The infants could be generating more intraoral pressure when feeding on the thick milk, and/or the xanthan‐thickened milk could be undergoing shear thinning (Lavoisier et al, 2021). In this case, we cannot evaluate the possibility of each, as the two are confounded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics and effectiveness of Gloup for pill dysphagia are well established 12. Fluoroscopy studies have demonstrated its superiority over water and other food vehicles in terms of tablet transit time 13.…”
Section: Introductionmentioning
confidence: 99%
“…In organizing this special issue, our main consideration has been on the fundamental principles and feasible techniques of texture modification for adult dysphagia. For this purpose, a number of leading scientists have been approached for a contribution in topics including the effect of bolus rheology of texture-modified foods on the degree of modification (Stading, 2021a); relationship between masticatory variables and bolus characteristics of meat with different textures (Pematilleke, Kaur, Adhikari, & Torley, 2021); textural properties and muscle activities during mastication of normal and ultrasonically softened sticky rice (Wattanapan, Saengnil, Niamnuy, Paphangkorakit, & Devahastin, 2021); extensional rheology and tribology of polysaccharide solution (Funami & Nakauma, 2021); the physical properties of texture-modified foods (Stading, 2021b); the effect of the rheological properties of thickened fluids on the in vitro swallowing of solid oral dosage forms (Lavoisier, Shreeram, Jedwab, & Ramaioli, 2021); and microwave treatment to modify textural properties of high-protein gel applicable as dysphagia food (Pure, Yarmand, Farhoodi, & Adedeji, 2021).…”
mentioning
confidence: 99%